2009
DOI: 10.2514/1.40300
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Traffic Flow Optimization with Tactical Flight Control Heuristics

Abstract: A sequential optimization method is applied to manage air traffic flow under uncertainty in airspace capacity and demand. To support its testing, a decision support system is developed by integrating a deterministic integer programming model for assigning delays to aircraft under en route capacity constraints to reactively account for system uncertainties. To reduce computational complexity, the model assigns only departure controls, while a tactical control loop consisting of a shortest path routing algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…For the ration-byschedule (RBS) models (rows 2-4), F(t) is ordered by increasing scheduled departure times, and flights are scheduled subject to the airport and sector capacity constraints defined in Eqs. (1)- (3). Note that the greater than signs in Eqs.…”
Section: Atsp Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…For the ration-byschedule (RBS) models (rows 2-4), F(t) is ordered by increasing scheduled departure times, and flights are scheduled subject to the airport and sector capacity constraints defined in Eqs. (1)- (3). Note that the greater than signs in Eqs.…”
Section: Atsp Planningmentioning
confidence: 99%
“…This contour level is being used, because Ref. 4 showed that these are reasonable representations of the regions of airspace that flights typically avoid.…”
Section: Atsp Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches don't usually fit the structure described in section 3.1. A flight path minimising the costs of a flight can be computed using dynamic programming [23], genetic algorithms [54], heuristic search algorithms [28], or a combination of both genetic algorithms and heuristic search [90]. Another way of minimising the costs of the flight consists on transforming the trajectory optimization problem into a non-linear programming problem that can be solved using various techniques.…”
Section: Other Approaches To Trajectory Predictionmentioning
confidence: 99%
“…Some of the most simple representations used in the literature include a two-dimensional (2D) position in the vertical plane [23,24] or in the horizontal plane [25][26][27][28]. The former are useful in the context of optimization in the vertical profile, while the latter can be used for optimizing traffic.…”
Section: Specification Of Trajectoriesmentioning
confidence: 99%